Finite p-groups which are not generated by their non-normal subgroups - Janko, Zvonimir (Glasnik matematički, 2016)
Here we classify finite non-Dedekindian p-groups which are not generated by their non-normal subgroups. (Theorem 1).
DOI funktioniert nicht
Gesehen am 22.02.2018